Inca Ayllus, lands of the Sun and water of Huanacauri in Sucsu Auccaille, San Jerónimo, Cusco - Escalante, Carmen (2020)
We deal with the transformation of the social group of Sucsu Auccaille, from having a type of socio-economic and political organization under the Inca State, to passing under Spanish rule and using written documentation and Spanish legislation to defend its possession over the land and maintain its unity as a social group. Within it, we are also interested in the role played by the descendants of the Incas who were rulers. It is a story of their land ownership, their struggles, and their continuity. We rely on ten colonial documents, referring to lands of the current peasant community of Sucsu Auccaille, and on interviews with community members, directors, and former directors of Sucsu Auccaille, in San Jerónimo. The Inca ethnic group was composed of several ayllus or lineages, two of them were Sucsu and Auccaille. At the beginning of the colonial era, these two were reduced in San Jerónimo: Sucsu, the panaca or lineage of the Inca Huiracocha, and Auccaille, the panaca or lineage of the Inca Yahuar Huaccac. With n its territory are the sacred places Tuynu, Osccollo, Andamachay, Aqhamana, the lands of the sun and the Huanacauriue stream; they are still cared for, with stealth and veneration (to mother earth and father mountain Huanacauri)